'The office of disaster management' nurse managers' experiences during COVID‐19: A qualitative interview study using thematic analysis. (12th August 2021) - Jackson, Jennifer; Nowell, Lorelli
Abstract: Aim: The purpose of this study was to understand the experiences of nurse managers during the COVID‐19 pandemic. Background: There is a growing body of knowledge about the experiences of clinical nurses during COVID‐19. However, there is less evidence about the experiences of nurse managers during the pandemic. Methods: Eight nurse managers, from acute care and outpatient settings, completed semistructured interviews about how their roles had changed during the pandemic, how they felt about these changes, and what had gone well or been difficult. Each participant was interviewed once, for 20–60 min. We used thematic analysis methods to analyse the interview transcripts. Findings: Nurse managers had to coordinate care in a context of uncertainty and guidance that changed frequently. Participants found that their roles and responsibilities either expanded to include more duties, or they were asked to take on a completely new role, with no orientation or training. Nurse managers were expected to provide support to their staff and patients, but did not necessarily receive support themselves. Participants were expected to plan simultaneously for care during the pandemic and for a return to normal working conditions. These factors contributed to challenging and difficult participant experiences of managing during COVID‐19. Conclusion: Nurse managers' experiences during COVID‐19 are influenced by changes to their roles and the support they received. Nurse managers continue to support high‐quality care despite working a difficult context. Implications for nursing management: Where possible, nurse managers can be supported to extend their roles or receive additional education and support if they are required to take on new responsibilities. Nurse managers require support in order to be a resource for their staff.